Babunyi: Recomposition of Materak Art in Minimalist Music Concept - Al Mubaraq, M. Habib; Panggabean, Della Rosa; Anggraini, Nora; Putra, Vindo Alhamda (Scoring: Journal of Film Music, 2025)
The musical composition “Babunyi” (a recomposition of Materak art in the minimalist music concept) is inspired by one of the kompang patterns found in Materak art, specifically the Kurang 1 pattern, which consists of the Induk (parent), Anak 2 (second child), and Anak 3 (third child) patterns. The concept of "Babunyi" utilizes a minimalist music approach, processed using the harmonic minor scale, and will be realized in a mixed ensemble format. The creation method for this work consists of three stages: exploration, experimentation, and realization. There are three structural processes in this composition: I (restricted pitch and rhythm materials), II (phasing), and III (long duration). The conclusion drawn is the use of minimal patterns followed by gradual changes until a complete musical composition is achieved.  Keywords : Materak, Kompang, Kurang 1, Minimalist Music, Mixed Ensamble.